Self-checkout accessibility: investigating usability barriers and ease of use for mature customers in grocery stores - Hashim, Siti Arlia (2025)
Self-checkout systems (SCSs) have increasingly become an inevitable feature in grocery retail environments as part of a broader shift towards technological innovation. However, little is known about how mature customers navigate these systems and how their experiences are shaped by the specific usability barriers they encounter. This research project aims to fill this gap by investigating the specific challenges older adults face when using SCSs and understanding how these barriers affect their overall shopping experience and satisfaction. The objective is to provide key insights that will enable retailers and developers of self-checkout technologies (SCTs) to create more user-friendly systems, particularly for mature customers who may find SCSs less intuitive than younger generations. Through a focus on inclusive design, grocery retailers can tap into the "Silver Economy," a growing demographic with significant spending power, and improve accessibility and satisfaction among older users.